Working and ageing : the benefits of investing in an ageing workforce - Barabasch, Antje [Mitarbeiter]; Dehmel, Alexandra [Mitarbeiter]; Van Loo, Jasper [Mitarbeiter] (Publications Office of the European Union, 2012)
"Slowly but steadily, in Europe, the attitude towards population ageing is changing. Early reports saw it as a demographic time bomb that would have negative consequences for economies and societies. More recently, the opportunities that population ageing brings with it have been emphasised, and the emerging silver economy is increasingly seen as a driver of future growth and prosperity. Lifelong learning is a crucial condition for active ageing and working longer. The year 2012, the European year for active ageing and solidarity between generations, supports lifelong learning and active ageing. This publication contributes to the debate by providing new insights based on the latest results from research and best practices in Europe and the Member States. It considers the benefits of and barriers to investing in learning later in life, presents emerging models of age-management in organisations and sectors, and examines international and interdisciplinary perspectives on working, ageing and learning. The evidence points towards the importance of showing the benefits of learning, developing demographic literacy in organisations and expanding the evidence base on the value of learning later in life using interdisciplinary research." (Hrsg., BIBB-Doku)
Keywords: G 1.1.1 Demografie; G 1.2 Arbeitsmarkt; P 1.8 Ältere; I 2.2 Europa; Demografischer Wandel; Arbeitswelt; Arbeitsmarkt; Älterer Arbeitnehmer; Lebenslanges Lernen; Berufliche Weiterbildung; Bildungsinvestition; Bildungsertrag; Europa